School Safety Concerns and Solutions: A Qualitative Analysis of U.S. School Psychologists’ Perspectives - Luz E. Robinson; Kate R. Watson; Natalie Fensterstock; Sawyer Hogenkamp; Yinuo Xu; Hannah Garner; Vanessa R. Warri; Casie H. Morgan; Anthony A. Garcia; Chaoyue Wu; Danielle Dunn; Dorothy L. Espelage; et al. (Behavioral Sciences, 2025)
In the present study, we analyzed qualitative survey data from 538 school psychologists across schools in the United States regarding their perceptions of school safety issues and potential strategies to address school safety. There are only a few studies exploring the experiences and perspectives of school psychologists that have been based on large-scale qualitative data. Using inductive coding, three themes for safety concerns emerged: (a) aggressive behaviors from students, (b) mental and behavioral needs, and (c) limited staffing. Three themes also emerged for potential solutions: (a) professional development/training, (b) school–family–community relationships, and (c) threat assessments. These findings from school psychologists have implications for addressing structural issues to prevent school violence in research and practice. Policy recommendations to inform resource allocation and improve school safety are discussed.